A Study of Intellectual Capital Influence on Financial Performance at Retailer Stores - Besar Ibrahim Mohammed (Eurasian Journal of Management & Social Sciences)
The primary goal of this study is to investigate the relationship between three major intellectual capital elements: human capital, structural capital, and relationship capital. A quantitative approach was used to assess the relationship between human capital and financial results in retail stores. A random sampling approach was used to determine the relationship between intellectual capital and financial results in retail stores. The study was carried out in Erbil’s Retailer shops. A total of 200 questionnaires were distributed in Retailer shops, but only 178 were obtained and properly completed, and the data was collected in hard copies. The authors used multiple regression analysis to assess the nine study hypotheses established by the authors. The results showed that the highest value was for the learning and education dimension’s relationship with a financial performance at retailer stores, whereas the lowest value was for experience and expertise’s relationship with a financial performance at retailer stores in Erbil.